Mortality Trends In Chandigarh (U.T) - Swami H.M; Bhatia S.P.S; Singh Kamaljit (Wolters Kluwer Medknow Publications, 1997)
Research question : With what causes people are dying in U.T. of Chandigarh? Objective: To analyse the causes of deaths that occurred in the years 1983and 1992. Study design: Record verification Setting: Urban, rural and slum areas Study Variable : Age, sex, residence, cause of death. Statistical analysis : Proportions Results : The death statistics of Chandigarh was comparable with that of the developed countries. The mortality due to infections and parasitic diseases had decreased from 18.7% to 12.3% in a decade whereas mortality from circulatory system diseases had increased from 18.1% to 31.2% in the same period.